X-ray spectrometry study on historical decorative glasses in thailand: Lanna-style glass - Pisutti Dararutana (2018)
It was known that historical objects were highly heterogeneous. Due to the complex nature of materials and objects, extremely sensitive, spatially resolved, multi-elemental and versatile analytical instruments were needed. The techniques employed should be as a noninvasive as possible and able to give complementary information from macroscopic to nanometer scales. In this work, X-ray based spectroscopy including energy dispersive X-ray fluorescence spectroscopy (EDS), Proton-induced X-ray emission spectroscopy (PIXE), and micro-beam X-ray fluorescence spectroscopy (μ-XRF) were used to analyze chemical composition of the Lanna-style glass. Microstructure was also studied. It can be concluded that these techniques in combination are powerful for the investigation of heterogeneous glassy materials. © (2013) Trans Tech Publications, Switzerland.